2013
DOI: 10.1016/j.athoracsur.2013.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Endothelial Cell Phenotypic Alterations in a Large Animal Model of Pulmonary Arteriovenous Malformations After the Glenn Shunt

Abstract: Background: Longevity of the superior cavopulmonary connection (SCPC) is limited by the development of pulmonary arteriovenous malformations (PAVM). The goal of this study was to determine whether phenotypic changes in pulmonary artery endothelial cells (PAEC) that favor angiogenesis occur with PAVM formation. Methods: A superior vena cava to right pulmonary artery connection was constructed in 5 pigs. Pulmonary arteries were harvested at 6-8 weeks following surgery to establish cultures of PAEC and smooth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
6
9
0
Order By: Relevance
“…One of the initial studies investigating hepatic factor and CHDassociated PAVMs reported that hepatocyte-conditioned media inhibited pulmonary artery EC proliferation. 16 This finding is consistent with the data reported by Kavarana et al 14 Kavarana et al reported that exclusive SVC blood flow in their pig model of SCPC physiology increased pulmonary artery EC proliferation compared to control ECs. 14 These results are in contrast to our finding that HV serum increases HPMEC proliferation compared to SVC serum.…”
Section: Discussionsupporting
confidence: 91%
“…One of the initial studies investigating hepatic factor and CHDassociated PAVMs reported that hepatocyte-conditioned media inhibited pulmonary artery EC proliferation. 16 This finding is consistent with the data reported by Kavarana et al 14 Kavarana et al reported that exclusive SVC blood flow in their pig model of SCPC physiology increased pulmonary artery EC proliferation compared to control ECs. 14 These results are in contrast to our finding that HV serum increases HPMEC proliferation compared to SVC serum.…”
Section: Discussionsupporting
confidence: 91%
“…[74] This study demonstrated that the pulmonary artery endothelial cells (PAEC) converted to a “proangiogenic” phenotype with PAVM formation (Figure 4B). These phenotypic differences in the PAECs from lungs with PAVMs included increased proliferation, tubule formation, and gene expression of proangiogenic factors such as angiopoietin-1 and TIE2 pathway.…”
Section: Introductionmentioning
confidence: 98%
“…These phenotypic differences in the PAECs from lungs with PAVMs included increased proliferation, tubule formation, and gene expression of proangiogenic factors such as angiopoietin-1 and TIE2 pathway. [74] Another group developed a porcine model of a bidirectional SCPC in which the RPA was ligated or banded. [75] They demonstrated that residual antegrade pulsatile flow following a SCPC prevented PAVM formation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations